Still another, and yet another Li Ran's re-writings of art history - a translational historiographical approach to global art history - Hopfener, Birgit (2021)
In his installations Mont Sainte-Victoire (2012) and Another ‘The Other Story’ (2013), contemporary artist Li Ran, who is based in China, poses questions about art historiographical frameworks of modern and contemporary art from a locally situated, transcultural perspective. Engaging with Li Ran’s historiographic art, Birgit Hopfener explores how he positions himself as subject to certain ‘realities’ of Chinese politics and art education, and discourses of global contemporary art. For Hopfener, Li Ran’s artworks also raise larger questions about the need for the historian to take into account a multiplicity of historiographical perspectives and models when practising history and art history in the global context. She thus reads Li Ran’s focus on modern and contemporary art’s relation to time and temporal epistemologies through the lenses of the Chinese literati tradition and recent discussions of transnational cultural studies and global art history as a practice of translation.. The first section of her chapter examines Li Ran’s practice as multi-perspectival, transcultural, and situated in a particular geo-cultural context. The second part treats Li Ran’s works in the tradition of Chinese literati art as an exercise and conceptualization of global art history as translational historiography.
Keywords: Li, Ran -- 1986-; Globalisierung; Kunstwissenschaft; Politik; Kunst; China